Tradução e adaptação transcultural da Celiac Self-Efficacy Scale para a língua portuguesa do Brasil - Silva, Leonardo Alexandrino (2020)
It aimed to translate and cross-culturally adapt the Celiac Self-Efficacy Scale into the Portuguese language of Brazil. It is a methodological study, following the four initial steps proposed by Beaton et al. (2007): initial translation, synthesis of translations, back-translation and review by a committee of experts. The study received approval from the UFC Research Ethics Committee under Opinion No. 3,355,172. The translation steps were performed from August to October 2019. In the first stage, a Spanish-Portuguese translation was performed by two bilingual professional translators with fluency in Spanish: a Brazilian registered nurse with declared fluency in Spanish (T1) and a teacher with Brazilian nationality, which was an official translator of Spanish (T2). In the second stage, the translations (T1 and T2) were synthesized by a master student, with experience in health technology development, who did not participate in the previous stage. In the synthesis process of the T1 and T2 versions to elaborate the T12 version of the 39 components of the scale, three cases of identical translations were obtained. In the absence of absolute agreement between the translations, the author performed, was follows: grouping words into 17 components of the scale to elaborate a single item in the T12 version; inserting ten terms and one comma in T12, which were not in either version of the initial translation; adding 14 complete components and three commas in the T1 version only; and inserting two complete components and a comma from version T2. Thus, the T12 version originated was sent for back-translation and evaluation by an expert committee. In the third stage, back-translation, the T12 version was translated into Spanish by an official Spanish translator with both Brazilian and Bolivian nationality and a Venezuelan translator which has an academic background in international relations. In the fourth stage, performed in November 2019, a committee composed of five members (a registered nurse; a PhD student in nursing, with experience in translation and cross-cultural adaptation of scale; a registered nurse with master degree, which was celiac; a Spanish teacher with Brazilian nationality, graduated in Portuguese-Spanish Literature; a Brazilian registered nurse with declared language proficiency, participant of the stage 1; and a Venezuelan translator, participant of stage 3). These experts evaluated the semantic, idiomatic, experiential and conceptual equivalences to produce the pre-final version of the scale by using a instrument with a three-point scale (1- adequate translation; 2- partially adequate translation; 3- inadequate translation) for each equivalence. It is noteworthy that the scale component was considered with an adequate translation when it received a score of 1. However, those considered with an inadequate translation were those scored with 2 or 3, where the suggestions of experts were registered and accepted in the pre-final version of the scale. In this stage, the equivalence adequacy percentages averages were: semantic (98%), idiomatic (94%), experiential (97%) and conceptual (100%), totaling 97.2% as a percentage mean of the total equivalence agreement. The Celiac Self-Efficacy Scale's translation and cross-cultural adaptation process has resulted in a promising instrument for use in Brazil.